The rise of populism within the Economic Freedom Fighters in South Africa: a theoretical case study of anti-establishment, economic inequalities and cultural backlash - Carstens, Joshua (University of Cape Town, 2021)
Populism is on the rise in many developed and developing countries and uprooting established party systems. In South Africa, research has shown that the Economic Freedom Fighters (EFF) can be seen as our turn towards populism, but what fuels the rise of the party? This dissertation argues that an anti-establishment stance entices citizens to vote for the EFF and economic inequalities and a cultural backlash makes our society fertile ground for a populist party. In this theoretical case study, international populism theory from especially Inglehart and Norris is applied to the local context to show why the aforementioned factors can explain the rise of populism.